Elements in the transcriptional regulatory region flanking herpes simplex virus type 1 oriS stimulate origin function. - Wong, S W (1991)
Like other DNA-containing viruses, the three origins of herpes simplex virus type 1 (HSV-1) DNA replication are flanked by sequences containing transcriptional regulatory elements. In a transient plasmid replication assay, deletion of sequences comprising the transcriptional regulatory elements of ICP4 and ICP22/47, which flank oriS, resulted in a greater than 80-fold decrease in origin function compared with a plasmid, pOS-822, which retains these sequences. In an effort to identify specific cis-acting elements responsible for this effect, we conducted systematic deletion analysis of the flanking region with plasmid pOS-822 and tested the resulting mutant plasmids for origin function. Stimulation by cis-acting elements was shown to be both distance and orientation dependent, as changes in either parameter resulted in a decrease in oriS function. Additional evidence for the stimulatory effect of flanking sequences on origin function was demonstrated by replacement of these sequences with the cytomegalovirus immediate-early promoter, resulting in nearly wild-type levels of oriS function. In competition experiments, cotransfection of cells with the test plasmid, pOS-822, and increasing molar concentrations of a competitor plasmid which contained the ICP4 and ICP22/47 transcriptional regulatory regions but lacked core origin sequences resulted in a significant reduction in the replication efficiency of pOS-822, demonstrating that factors which bind specifically to the oriS-flanking sequences are likely involved as auxiliary proteins in oriS function. Together, these studies demonstrate that trans-acting factors and the sites to which they bind play a critical role in the efficiency of HSV-1 DNA replication from oriS in transient-replication assays.